Development of the Methodology for Comprehensive Analysis of the Efficiency of the State Financial and Investment Model of Population Social Security Using the Example of Russian Regional Finance - M. L. Dorofeev (Финансы: теория и практика)
The effectiveness of financing the social security system is one of the key conditions for sustaining sustainable economic growth. The global economic crisis of 2020 associated with the coronavirus pandemic, and the subsequent crisis of 2022, due to the urgent need to carry out a structural transformation of the Russian economy in the context of large-scale international sanctions, emphasized the relevance of the problem of increasing the efficiency of budget expenditures on social policy. The purpose of the study is to develop methodological approaches to the comprehensive analysis of the effectiveness of the State financial and investment model of social security of the population (further — SFIMSS) using the example of data on the socio-economic development of the regions of Russia. The following methods were used: coefficient analysis, ranking, construction of heat maps and regression analysis. The coefficient of efficiency of budget expenditures at the regional level makes it possible to have fairly comprehensive assessments of the regions. The application of the regression analysis methodology makes it possible to expand its effectiveness and identify important dependencies and relationships on the basis of which it is able to establish the policy of state financial regulation. This study evaluated the effectiveness of 85 regions for the period from 2017 to 2021. The most and least effective regions were identified. The construction and interpretation of the regression model made it possible to identify a number of significant exogenous factors such as GRP, GRP per capita, volume indices of GRP, that positively impact the effectiveness of SFIMSS. At the same time, the public debt on loans in rubles, the volume of budget expenditures on social support measures for certain categories, and the proportion of the population older and younger than working age have a negative impact. In the article, recommendations are given on the development of mechanisms for increasing the efficiency and targeting of budget expenditures, as well as the creation of conditions to accelerate economic growth in regions, which will increase the effectiveness of SFIMSS.